License analysis of e-Journal perpetual access - Zhang, Mei; Eschenfelder, Kristin (The Journal of Academic Librarianship, 2014)
In this paper we investigate the definitions of perpetual access and examine current studies on the attitudes and concerns towards perpetual access from both libraries and publishers separately. We then conduct a content analysis of 72 e-journal licenses to explore whether perpetual access clauses vary among commercial publishers and non-commercial publishers, whether clauses change over time, and whether differences exist between consortium and site licenses. Results suggest that different perpetual access clauses may be at different stages of institutionalization. Perpetual access clauses that are more institutionalized include: addressing perpetual access in license, providing perpetual access upon expiry of subscription, and specifying a location for perpetual access.
Keywords: perpetual access; licensing; e-journals; scholarly publishing; electronic publishing; institutionalization